2010
DOI: 10.4269/ajtmh.2010.09-0426
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Potential Risk Areas of Human Plague for the Western Usambara Mountains, Lushoto District, Tanzania

Abstract: Abstract. A natural focus of plague exists in the Western Usambara Mountains of Tanzania. Despite intense research, questions remain as to why and how plague emerges repeatedly in the same suite of villages. We used human plague incidence data for 1986-2003 in an ecological-niche modeling framework to explore the geographic distribution and ecology of human plague. Our analyses indicate that plague occurrence is related directly to landscape-scale environmental features, yielding a predictive understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…Already previous studies in the area have shown that every plague outbreak was preceded by rodent outbreak (Kamugisha et al, 2007). Similar results have been reported by Neerinckx et al (2010) and Eisen et al (2012) in Tanzania and Uganda, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Already previous studies in the area have shown that every plague outbreak was preceded by rodent outbreak (Kamugisha et al, 2007). Similar results have been reported by Neerinckx et al (2010) and Eisen et al (2012) in Tanzania and Uganda, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies in the West Usambara Mountains in Lushoto Tanzania have shown a large diversity of small mammals and fleas implicated as plague hosts and vectors, respectively (Kilonzo & Msangi, 1991;Laudisoit et al, 2007). Furthermore, Kamugisha et al (2007) and Neerinckx et al (2010) have found that plague reported cases were located at elevations above 1,500m in Lushoto, Tanzania. Similar results have been reported in Uganda that plague cases are common in areas above 1300m (MacMillan et al, 2011;Eisen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such patterns are consistent with observations made in other contexts. 26,53 Rodent species other than M. natalensis also exhibited strong affinities for particular land-use types. However, all five rodent species captured in agricultural sites were also detected in conserved sites.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several statistical models have been constructed using geographic information system (GIS)-based and remotely sensed (RS) data to evaluate landscape variables that are associated with plague risk and attempt to explain this spatial heterogeneity. 10,[12][13][14][15][16][17] For example, within the West Nile region of Uganda, which is the primary epidemiologic focus within that country, 18 a fine resolution GIS-based model revealed that areas of higher elevation (above 1,300 m) that are wetter, with less vegetative growth and more bare soil during the dry month of January, pose an elevated risk of plague occurrence. 12 Such models are useful for identifying areas of elevated risk based on landscape variables, which aids in targeting limited public health resources.…”
Section: Introductionmentioning
confidence: 99%